Extension Service Consumer Factsheet: "Paper or Plastic?" - Kenneth R. Berger (EDIS)
The true environmental impact of these packages parallel their monetary cost rather closely. In either case, using the paper sack or the plastic bag multiple times before it enters the waste stream is the best choice you can make when deciding between "paper or plastic." This document is ABE329, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published December 2002.